Hacı Şerîatullah ve Ferâiziyye hareketi - Abedin, Minhazul (My University, 2021)
İngiliz sömürge dönemi (1757-1947) İslamiyet sonrası Hint alt kıtası tarihi için oldukça önemli bir dönemdir. Bölgede daha önce hâkim olan Müslümanların İngilizlere yenilmeleri sonucunda müslümanlar arasında ortaya çıkan dinî ve siyasî istikrarsızlıklar, Hint alt kıtası müslüman fikir dünyasında bu duruma bir tepki olarak doğan ve radikal etkiler meydana getiren çok sayıda hareketin ortaya çıkmasına neden olmuştur. İngiliz sömürgedöneminde Hint alt kıtasında ortaya çıkan hareketlerin başında ise kuşkusuz Hacı Şerîatullah’ın liderliğinde Bengal bölgesinde ortaya çıkan Ferâiziyye hareketi gelmektedir. Ferâiziyye hareketi, bir taraftan İngilizlere karşı mücadelede önemli rol oynaması diğer taraftan ise müslümanların dinî ve siyasî hayatına olan etkisi bakımından Müslüman Hint alt kıtası tarihi önemli bir yere sahiptir. Bu tez Hacı Şerîatullah’ın hayatı, fikirleri, İngiliz hükümetine karşı tutumu, Ferâiziyye hareketi; hareketin doğuşu, arka planı, gayesi, özellikleri, Bengal müslüman topluluğuna olan etkisini ele almayı amaçlamaktadır. Ayrıca Hanefiliğin hâkim olduğu bölgede, Vehhabî düşüncelerinden etkilenen bir harekete Bengal müslümanlarının ilgileri ve sonraki dönemlerde bölgedeki İslamî fikir dünyasında hareketin izleri analiz edilmiş, bu hareketin Bengal-Müslüman topluluğuna etkisi tespit edilmeye çalışılmıştır.

The British colonial period (1757-1947) was a very important period for the Muslim history of Indian sub-continent. During this period, the Indian sub-continent, which reacted to the religious and political instability among Muslims as a result of the loss of the place of the predominantly Muslims in the region to the British, witnessed many movements that left radical effects on the Muslim world of ideas. One of the events that emerged in the Indian sub-continent during the British colonial period was undoubtedly the Feraiziyya movement that emerged in the Bengal region under the leadership of Haji Shariaullah. The Feraiziyya movement has an important place in the history of Islam in the Indian sub-continent in terms of its reaction to the British, its influence on the religious and political life of Muslims. The importance of the Haji Shari'atullah and Feraiziyya movement in terms of the Indian sub-continent Islamic history and its impact on the Bengali Muslim community encouraged us to choose Haci Shariatullah: His Life, the Feraiziyya Movement and the Impact on the Bengali Muslim Community. Our study, which aims to deal with Haci Shari'atullah's life, his idea, his attitude towards the British government, the Feraiziyya movement, the necessity of such a movement at the time, the background, the characteristics, especially the influence on the Bengali Muslim community, The movement will show the Muslims' interest in Bengal, and in later periods will understand its traces in the world of Islamic ideas in the region and will try to identify its influence on the Bengali-Muslim community. The tool will be Turkish, but Bengali, English, Arabic, Urdu and Persian sources will also be used. The international method will be adopted in formulating this research perspective by following the historical, descriptive, analytical and observational steps of effective research.
Keywords: Bengal; British; Colony; Çivit Ziraatçi; Dudu Miyan; Duzu Miyân; Faraizi; Ferâiziyye; Hacı Şerîatullah; Haji Shariatullah; Hindistan; History; India; Indigo Planters; Islam; İngiliz; İslam; Sömürge; Tarih; Zamindars; Zemindâr